Elevated Homocysteine Levels and Vitamin Deficiencies as Potential Risk Markers for Coronary Artery Disease in Apparently Healthy Adults - K. Sowndarya; Anupama Hegde; Neelam M. Pawar; Ramya Shenoy (Biomedical and Biotechnology Research Journal)
Background: Hyperhomocysteinemia (HHcy) is proposed as a risk factor for coronary artery disease (CAD), while dyslipidemia is a well-established risk factor. HHcy can arise from deficiencies in Vitamin B12 (Vit B), Vitamin B6, and folic acid (FA), as well as from kidney diseases or genetic factors. This study aims to evaluate homocysteine (Hcy) levels as potential predictors of CAD risk in apparently healthy adults. Methods: A cross-sectional analytical study was conducted with 62 healthy individuals aged 20–62 years visiting a tertiary healthcare center for routine health checks. After obtaining ethical clearance and informed consent, serum Hcy levels, fasting lipid profiles (total cholesterol, triglycerides, high-density lipoprotein, and low-density lipoprotein), Vit B12, and FA levels were measured using standard laboratory techniques. Statistical analyses were conducted using SPSS version 20. Results: HHcy was detected in 43.54% of participants, with 59% of those exhibiting either isolated or combined vitamin deficiencies. A significant negative correlation was found between Hcy levels and both Vit B12 and FA (P < 0.001). Notably, there was no significant correlation between Hcy levels and traditional lipid profile markers. Conclusion: The findings indicate that apparently healthy adults can have elevated Hcy levels significantly associated with Vit B12 and FA status, but not with conventional CAD risk markers such as lipid profiles. These results suggest the need for further investigation into Hcy as a viable alternative marker for CAD risk in young adults, emphasizing the importance of monitoring vitamin levels to mitigate cardiovascular risks.